Create Fat Substitute From Soybean Protein Isolate/Konjac Glucomannan: The Impact of the Protein and Polysaccharide Concentrations Formulations - Huang, Lu; Ren, Yuqing; Li, He; Zhang, Qibo; Wang, Yong; Cao, Jinnuo; Liu, Xinqi (Frontiers in Nutrition, 2022)
In this study, soybean protein isolate (SPI) and coconut oil were emulsified and konjac flour was added to prepare the protein/polysaccharide composite emulsion gel. The SPI/polysaccharide compound fat substitute was obtained by vacuuming. The effects of protein and konjac flour addition on the gel system of the mixed emulsion were explored. Sensory evaluation experiments showed that the overall acceptability of fat substitutes added with 1% SPI was higher. With the increase of protein and konjac content, the juiciness of the samples decreased gradually. The increase of konjac content reduced the brightness of compound fat substitutes, and the yellowness of compound fat substitute increases significantly with the increase of protein content. The rheological results showed that the G′ and loss modulus (G″) increased with the increase of protein and konjac content, forming a rigid elastic gel matrix, which provided a basis for the preparation of fat substitutes. Texture profile analysis (TPA) results showed that the springiness of all samples was similar to the natural fat after 20 min of heating. With the increase of protein and konjac content, the hardness of the samples increased gradually. The results of oral tribology showed that the friction coefficients of all samples were very small. The friction behavior of the samples with SPI content of 1% was similar to that of natural fat, which could better simulate the swallowing feeling and lubricity of natural fat. To sum up, the appearance of solid fat substitutes prepared with SPI and konjac flour is similar to pork fat. They show ideal functional characteristics in mechanical properties and oral tribology. Among them, the fat substitute with the protein content of 1% and konjac content of 4% is the most popular among consumers.